2018
DOI: 10.1021/acs.jafc.8b05692
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered Sorbents To Increase the Persistence of the Allelochemical Carvone in the Rhizosphere

Abstract: This study investigates the changes in sorption/desorption, dissipation and leaching of the two enantiomeric forms of the allelochemical carvone, R-carvone and S-carvone, after amending an agricultural soil sample with two nanoengineered sorbents: biochar (BC) and organoclay (OCl). The sorption of carvone enantiomers was non-enantioselective and similarly improved by the addition of OCl and BC to the soil. However, OCl-amended soil showed reversible sorption, whereas BC-amended soil displayed sorption-desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…Since allelochemicals can display a poor stability in aqueous solution and/or soil extracts, it is important to test their storage stability to avoid analytical artefacts when conducting experiments to assess their behaviour in soils 24,49 . The stability of umbelliferone in different water/methanol mixtures exposed to light and under dark conditions is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since allelochemicals can display a poor stability in aqueous solution and/or soil extracts, it is important to test their storage stability to avoid analytical artefacts when conducting experiments to assess their behaviour in soils 24,49 . The stability of umbelliferone in different water/methanol mixtures exposed to light and under dark conditions is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of light exposure and presence of soluble soil components on the storage stability of umbelliferone was studied for umbelliferone aqueous solutions containing different amounts of methanol, which was used as a stabiliser. High concentrations of alcohol have antimicrobial properties 48 and previous experiments had shown that the addition of methanol helped stabilise aqueous solutions of readily biodegradable organic compounds, presumably by eliminating microbial activity 24,49 . For the stability experiments, 2 mg L −1 umbelliferone solutions (100 mL) were prepared either in distilled water or in a soil extract.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil dissipation of coumarin was very fast for both doses tested, which is typical of natural allelopathic compounds and is the main drawback for their potential use as biopesticides 50 . For this reason, strategies to increase their persistence in soils are vitally needed 8,9,40 …”
Section: Discussionmentioning
confidence: 99%
“…The use of different tools based on nanotechnology could overcome some of these limitations enhancing their effectiveness 6 . For instance, nanoengineered sorbents can be applied to soils to reduce the mobility of these compounds, 8,9 or nanoformulations of natural products can be prepared to protect them from premature degradation 10,11 . The application of adjuvants could be another strategy to improve the effectiveness of allelochemicals in soils.…”
Section: Introductionmentioning
confidence: 99%